Perjuangan Perempuan untuk Memperjuangkan Persamaan di "Mother Courage and Her Children" Drama oleh Brecht - Simamora, Juita; Satria, Robby (BASIS (Bahasa dan Sastra Inggris), 2022)
This research shows gender inequality in the drama Mother Courage and Her Children, feminism dominates the male role. With this domination Mother's courage lived in the nineteenth century, when patriarchal customs were still firmly held by the community. Women were still enslaved by male superior and the character of the Mother Courage opposes her domination by doing various struggles. This research uses feminist existentialism (Beauvoir S. , 1949) encourages women to step outside the boundaries and social circles that make them lose their freedom for themselves. This research is a qualitative research that produces descriptive data. This study uses content analysis techniques, starting with looking for similarities in data, combining them into a single unit in subchapters, critical and evaluative studies with the help of Beauvoir's social theory. The researcher's findings regarding the movements described in the play "Mother Courage and Her children" are as follows: In the study of women's struggles, Simone de Beauvoir's theory is highly valued because women are involved in various struggles in an effort to overcome themselves. The result show women can improve themselves in the face of gender inequality that is driven by men. This shows when women struggle to prove that women are capable of working, intellectually capable, capable of being fearless women and also able to resist public policies.